The Threshold Effect in Expected Volatility: A Model Based on Asymmetric Information - Longin, François M. (Review of Financial Studies, 1997)
This article develops theoretical insight into the effect in expected volatility, which means that large shocks are less persistent in volatility than small shocks. The model uses the Kyle-Admati-Pfleiderer setup with liquidity traders, informed traders, and a market maker. Information is modeled as a GARCH process. It is shown that the GARCH process for information is transformed into a TARCH process (for threshold GARCH) for the market price changes. Working with information flows allows one to derive implications for trading volume and market liquidity which provide the basis for a more complete test of the model. Article published by Oxford University Press on behalf of the Society for Financial Studies in its journal, The Review of Financial Studies.